Najd-Qatari Relations 1916-1517 (Journal of the College of Basic Education, 2022)
The research is based on its hypothesis on the historical origins of the relations between Qatar and Najd throughYears of modern history and in several magazines; and an attempt to delve into the modern history of Qatar; And howDespite its small size and small population, it was able to make its way after the unification of its tribes.The forces of another neighboring tribe wanted to impose control on it and make it subordinate to Haa, and it was alsoIt intends to extend its influence to include most of the eastern regions of the Arabian Peninsula.The study will attempt to follow the emergence of the Salafist movement, which had a great impact on the establishment of the stateThe first Saudi Arabia since the middle of the eighteenth century and to know what the wide changes it brought aboutIn the modern and contemporary history of the Gulf and the Arabian Peninsula, while monitoring the Najdi movements towards Qatarthat began at the end of the century,